Cultural identity in K. S. Maniam's Ratnamuni - Babaee, Ruzbeh; Sedehi, Kamelia Talebian; Talif, Rosli (Universiti Putra Malaysia Press, 2015)
In his fiction, the Malaysian-Indian author, K. S. Maniam depicts the identity and culture of Malaysian-Indian. This is shaped with a collection of materials that are vital to keep the trace of ancestral identification marks, of retaining the status of being Indian, even though the land they live in is not India. In the new land the Indian community invests its new narrative of existence with a power structure to support the Diasporic Indian “self”. In Maniam’s reconstruction of the Indian immigrant experience in Malaysia, there are the difficulties that the community faced when trying to recreate this world. Maniam depicts the rites of the complicated cultural issues in a Diasporic Indian community. In his reconstruction of the Indian immigrant experience of Malaya, One can see these previously peripheral characters as the agents of the Diasporic identity that the present day Malaysian-Indian has inherited. The passage of such identity formation, however, is demonstrated to be filled with the many snares of both colonial and postcolonial experiences. The present study examines Maniam’s short story, Ratnamuni, from a Diaspora perspective. This study shows the way in which Maniam symbolically depicts the culture of a nation in Diaspora.